Pengaruh Video Pembelajaran Dengan Model Discovery Learning Materi Suhu Dan Kalor Untuk Meningkatkan Aktivitas Siswa - Sandhi Setya Praptama; Wahyudha Tri Setiyoaji; Endang Purwaningsih (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
The aim of this study was to determine the effect of using video-based media on the activities and learning outcomes of physics class X on the subject of temperature and heat at SMK Negeri 1 Grat. As a source of learning, technology is a tool to facilitate learning that is more interesting for students, among the many learning technologies, one of them is video media, which has advantages that are quite good for the implementation of learning. Experimental research used in this research is a quasi-experimental (Quasi Experimental Design) using the Nonequivalent Control Group Design. This design has a control group, but it cannot function to control external variables that affect the implementation of the experiment. Subject of this research are 25. There is a significant effect of using video-based learning media on students' learning activities. Obtained results, the responsibility of students when using video media with the OBS system application obtained an average of 62,25% at pretest and 82,67% at posttest, it can be concluded that students are more active in the experimental class than in the control class.